The Effect of the Use of Cervical Collar on the Reduction of Neck Pain: Meta-Analysis - Syafi’ie, Hisyam; Prasetya, Hanung; Murti, Bhisma (Indonesian Journal of Medicine, 2021)
Background: Neck pain is the fourth leading cause of disability, with an annual prevalence rate exceeding 30%. Nearly 50% of individuals will continue to experience pain or it often occurs to some degree. This study aimed to analyze the magnitude of the effect of using a cervical collar on reducing the degree of pain in neck pain patients compared to manual therapy (exercises).Subjects and Method: This research is a systematic review and meta-analysis carried out by following the PRISM diagram flow. The process of searching for articles through a journal database that includes: PubMed, Google Scholar and Science Direct by selecting articles published in 2000-2020. The keywords used include: “cervical collar” OR “neck collar” OR “soft collar” OR “hard collar” AND “neck pain” AND “cervical pain” AND “cervical radiculopathy” AND “cervical syndrome” AND “randomized controlled trial”. The inclusion criteria were full paper articles with a randomized controlled trial study design, articles using English and Indonesian, and bivariate analysis with adjusted odds ratio. Articles that meet the requirements are analyzed using the Revman 5.3 application.Results: A total of 6 articles were reviewed in this study with a randomized controlled trial study design. Meta-analysis of 6 randomized controlled trial (RCT) studies showed that there was no difference in effectiveness in using cervical collars compared to manual therapy (exercises) in reducing neck pain (ES = 0.04; 95% CI -0.31 to 0.39; p = 0.083).Conclusion: This meta-analysis concluded that there was no difference in effectiveness between the use of cervical collars and manual therapy (exercises) in reducing the degree of pain in neck pain.Keywords: neck pain, cervical collar, exercises,meta-analisisCorrespondence: Hisyam Syafi’ie. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: bunghifi@gmail.com. Mobile: 081326002006.Indonesian Journal of Medicine (2021), 06(01): 112-118https://doi.org/10.26911/theijmed.2021.06.01.12